Vaccination Status of OPV0 and BCG in Preterm Infants and Associated Factors in Southwestern Uganda: - Namiiro,Agnes; Ochora,Moses; Keneema,Olive; Muwanguzi,Moses; Tugumenawe,Darius; Faith, DoreenLonges; Yusuf,Ibrahim; Tagema, Fiona; Mwinike ,Yusuf; Kumbakumba, Elias (Pediatric Health, Medicine and Therapeutics, 2026)
Background: Despite the high Uganda National target of 90% for Bacillus Calmette-Guerin (BCG) and birth dose Oral Polio Vaccine (OPV0), preterm infants in Uganda remain at increased risk for vaccine preventable diseases due to delayed or missed early vaccination. The delay may be a result of poor understanding of the safety and effectiveness of vaccines. The exact estimate of preterm infants vaccinated, the vaccines missed or delayed and drivers of this vaccination status are not well studied in Southwestern Uganda. This study therefore determined the vaccination status of BCG and OPV0 in preterm infants and associated factors in the Southwestern region. Methods: We conducted a cross-sectional quantitative study between May and September 2023 at Mbarara Regional Referral Hospital and Holy Innocent Children’s Hospital. We consecutively recruited 350 preterm infants and their caretakers as they attended the newborn follow-up clinic and extracted data from their medical records. We described the vaccination status and used logistic regression model to determine associated factors. Results: The median age of preterm infants was 13 weeks Interquartile range (IQR), 4–26 and the median birth weight was 1.6kg, IQR, 1.3–1.8 at the time of the study. Two-thirds 66.6% (233/350) of our preterm infants had received both BCG and OPV0. More preterm infants 65.4% (229/350) had received BCG than OPV0 28% (98/350). Increasing preterm infant age, regular maternal antenatal care attendance and hospital discharge recommendation of vaccination increased the likelihood of vaccinating a preterm infant. However, denial of vaccination at first presentation negatively influenced vaccination of preterm infants. Conclusion: The vaccination status of BCG and OPV0 among preterm infants in the greater part of Southwestern Uganda is below the national target. Consequently, interventions are needed to improve timely vaccination rates among preterm infants before hospital discharge.
A Cross-Sectional Study
Keywords: vaccination; preterm infants; Southwestern Uganda